2018
DOI: 10.1097/md.0000000000013007
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects between 2 computerized cognitive training programs, Bettercog and COMCOG, on elderly patients with MCI and mild dementia

Abstract: Background:A computerized cognitive rehabilitation program can be used to treat patients with mild cognitive impairment or dementia. We developed a new computerized cognitive rehabilitation program (Bettercog) that contained various treatment programs for cognitive training for mild cognitive impairment or dementia. This study was conducted to compare the clinical efficacy of Bettercog and computer-assisted cognitive rehabilitation (COMCOG) that has had clinical efficacy previously proven in patients with mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 7 publications
4
45
0
Order By: Relevance
“…Six records were excluded because they did not report any outcomes that were directly related to social participation or self-management [ 61 , 62 , 63 , 64 , 65 , 66 ]. Four records reported on BADLs only [ 67 , 68 , 69 , 70 ]. Three studies were excluded because although participants with some form of cognitive impairment were included in the study, the outcomes were not reported separately from outcomes from those who were either cognitively healthy or had other pathologies [ 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six records were excluded because they did not report any outcomes that were directly related to social participation or self-management [ 61 , 62 , 63 , 64 , 65 , 66 ]. Four records reported on BADLs only [ 67 , 68 , 69 , 70 ]. Three studies were excluded because although participants with some form of cognitive impairment were included in the study, the outcomes were not reported separately from outcomes from those who were either cognitively healthy or had other pathologies [ 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive function was evaluated using the Seoul Neuropsychological Screening Battery (SNSB-II) [ 24 , 25 ] by certified clinical psychologists who had at least 3 years of experience with administering the SNSB-II. Scores for attention, visuospatial function, memory, and frontal/executive function were calculated, and T-scores of each variable were used to analyze these factors.…”
Section: Methodsmentioning
confidence: 99%
“…However, when using CCR, it is difficult not only to systematically evaluate patients' cognitive level but also to induce interest and motivation for rehabilitation. In order to overcome these limitations, computer-based cognitive rehabilitation has been developed, and several studies have found it to be effective in improving the cognitive function of patients with neurological disorders and dementia and of older adults [11][12][13]. This therapeutic modality not only can systematically adjust the difficulties of the activities according to the cognitive level of the patient, but also has the advantage of using a variety of cognitive rehabilitation programs.…”
Section: Introductionmentioning
confidence: 99%